Lithium ion battery binder and preparation method thereof, lithium ion battery and power-related equipment

By developing a lithium-ion battery binder with a nuclear womb structure, the expansion of micron silicon silicon carbon anode material, SEI film instability and charge and discharge stress in lithium-ion batteries was solved, and better cycling performance and expansion suppression were achieved. Effect.

CN119463757APending Publication Date: 2025-02-18NEIJIANG EPNO NEW ENERGY TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411552690.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the expansion of micron silicon silicon carbon anode materials in lithium-ion batteries, SEI film instability and charge and discharge stress, resulting in a degradation of cycling performance.

Method used

A lithium-ion battery binder with a nuclear whisker structure has been developed, and its raw materials include hydrophilic monomers, hydrophobic monomers, functional monomers, reactive surfactants, non-reactive surfactants, initiators, and crosslinking agents. , chain transfer agent, lipophilic monomer and alkaline neutralizer, form flexible core and rigid structure through emulsion polymerization and in-situ polymerization technology to enhance adhesion and stress buffering capabilities.

Benefits of technology

The adhesive buffers the expansion stress through the flexible core, and the rigid structure enhances the bonding force between micron silicon particles, significantly improving the circulation performance of the lithium-ion battery and suppressing expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463757A_ABST
    Figure CN119463757A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery binder and a preparation method thereof, a lithium ion battery and power-related equipment, and relates to the technical field of lithium ion batteries. The lithium ion battery binder comprises the following raw materials: a hydrophilic monomer, a hydrophobic monomer, a functional monomer, a reactive surfactant, a non-reactive surfactant, an initiator, a cross-linking agent, a chain transfer agent, an oleophylic monomer, an alkaline neutralizer and water, the lithium ion battery binder is of a core whisker structure. The flexible core of the lithium ion battery binder can provide a buffer effect of stress caused by volume expansion change on the particle surface, and the rigid core prepared by the hydrophilic chain segment provides a strong binding force among micron silicon particles, so that active substances are not easy to desorb a current collector in circulation; the lithium ion battery binder can improve cycle performance and inhibit expansion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium-ion battery binder and a preparation method thereof, a lithium-ion battery and electrical equipment. Background Art

[0002] At present, the application of lithium-ion batteries in mobile electronic products, power batteries and energy storage is considered to be the mainstream development trend in various fields. With the development of various industries, the demand for increasing the energy density of lithium batteries has become increasingly significant, and thus silicon negative electrodes have come into being; the specific capacity of silicon negative electrodes can reach 4200mAh / g, which is much higher than the theoretical capacity of graphite 372mAh / g; in the development of the technical route of silicon negative electrodes, the current mainstream technical route of nano-silicon oxygen and nano-silicon carbon based on vapor deposition has achieved some commercial results.

[0003] However, this technical route is difficult to scale up, the preparation process is difficult to control, and silane gas is flammable and explosive, which seriously hinders the development of the silicon negative electrode industry. Therefore, silicon negative electrode technology based on micron silicon has received more and more attention. The technical route of micron silicon is easy to scale up for mass production, solving the industry problems in the direction of nano silicon. The problem with the micron silicon technical route is that it is more difficult to control expansion, more unstable SEI film, and greater stress changes in the charge and discharge system.

[0004] In view of the above situation, it is particularly important to develop binders and solutions suitable for micron silicon and silicon carbon made using micron silicon technology. However, there are currently no lithium-ion battery binders developed for micron silicon and silicon carbon negative electrodes on the market. Summary of the invention

[0005] The purpose of the present application is to provide a lithium ion battery binder and a preparation method thereof, a lithium ion battery and electrical equipment to solve the above problems.

[0006] To achieve the above objectives, the present application provides a first aspect of a lithium ion battery binder, the raw materials of which include:

[0007] Hydrophilic monomer, hydrophobic monomer, functional monomer, reactive surfactant, non-reactive surfactant, initiator, crosslinking agent, chain transfer agent, lipophilic monomer, alkaline neutralizer and water;

[0008] The lithium ion battery binder is a core-whisker structure.

[0009] Optionally, the lithium-ion battery binder satisfies at least one of the following conditions;

[0010] A. the hydrophilic monomer comprises a compound containing a carboxyl group and / or a sulfonic acid group;

[0011] B. the hydrophobic monomer comprises one or more of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, hexyl acrylate, hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, acrylonitrile, methacrylonitrile, glycidyl acrylate, glycidyl methacrylate, maleic anhydride, allyl glycidyl ether, glycidyl ethyl acrylate, dimethyl-m-isopropenyl-benzyl isocyanate, and methylene succinic anhydride;

[0012] C. the functional monomers include lower alkyl methacrylate, hydroxyalkyl (meth)acrylate, polyethylene glycol allyl ether, polypropylene glycol vinyl ether, polypropylene glycol allyl ether, polyethylene glycol methacrylate, polypropylene glycol methacrylate, C8-C30 alkyl methacrylate, dodecyl acrylate, lauric methacrylate, hexadecyl acrylate, octadecyl acrylate, behenyl acrylate, vinyl dodecanoate, vinyl hexadecanoate, vinyl octadecanoate, vinyl behenate, dodecyl vinyl ether, hexadecyl vinyl ether, octadecyl vinyl ether, behenyl vinyl ether, polyethylene glycol methacrylate, lauryl acrylate, polyethylene glycol methacrylate, octadecyl acrylate, one or more;

[0013] D. the reactive surfactant comprises one or more of allyloxy nonylphenol polyoxyethylene ether, allyl ether sulfonate, acrylamide sulfonate, maleic acid derivative, sodium allyl alkyl succinate sulfonate, allyl polyether, acrylic acid polyether phosphate, methacrylic acid polyether phosphate, alcohol ether phosphate containing double bonds, methacrylamide isopropyl sulfonic acid, methacrylamide isopropyl sulfonate, alkyl alcohol ether sulfate containing allyl, alkyl alcohol ether sulfate containing double bonds, dialkyl sulfosuccinate containing double bonds, vinyl sulfonate, sodium 1-propyleneoxy-2-hydroxypropane sulfonate, alkylpropylene phenoxy polyether sulfate, allyl polyether phosphate, and polyether ammonium phosphate containing double bonds;

[0014] E. The non-reactive surfactant includes one or more of aromatic aliphatic nonionic emulsifiers, aliphatic nonionic emulsifiers, anionic emulsifiers, cationic emulsifiers, and zwitterionic surfactants;

[0015] F. the initiator comprises one or more of ammonium persulfate, potassium persulfate, sodium persulfate, benzoyl peroxide, dodecyl peroxide, lauroyl peroxide, dicumyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, azobisisobutyronitrile, azobisisoheptylnitrile, tert-butyl hydroperoxide, sucrose, daunolide, sodium pyrosulfite, N,N-dimethylaniline, sodium bisulfite, tartaric acid, daunolide, ferrous sulfate, N,N-diethylaniline, ferrous pyrophosphate, silver nitrate, mercaptan, cumene hydroperoxide, ferrous chloride, tetraethyleneimine, and vitamin C;

[0016] G. the cross-linking agent includes one or more of butadiene, isoprene, divinylbenzene, dicyclopentadiene, divinylnaphthalene, N,N-methylenebisacrylamide, divinyl phthalate, sucrose polyallyl ether, pentaerythritol diallyl ether, pentaerythritol triallyl ether, pentaerythritol tetraallyl ether, trimethylolpropane diallyl ether, trimethylolpropane triallyl, and polyethyleneimine;

[0017] H. the chain transfer agent comprises n-dodecyl mercaptan;

[0018] I. The lipophilic monomer comprises one or more of acrylonitrile, methacrylonitrile, styrene, methyl acrylate, ethyl acrylate, n-butyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, isobornyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, vinyl acetate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and glycidyl methacrylate;

[0019] J. The alkaline neutralizing agent includes one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium carbonate, potassium hydroxide, calcium carbonate, calcium hydroxide, lithium carbonate, lithium bicarbonate, lithium hydroxide, and ammonia water.

[0020] Optionally, the lithium-ion battery binder satisfies at least one of the following conditions;

[0021] A. the hydrophilic monomer comprises one or more of acrylic acid, acrylic acid salt, methacrylic acid, methacrylic acid salt, allyloxyhydroxypropyl sulfonic acid, allyloxyhydroxypropyl sulfonic acid salt, vinyl sulfonic acid, vinyl sulfonic acid salt, 2-acrylamide-2-methylpropane sulfonic acid, propylene sulfonic acid, propylene sulfonic acid salt, methacrylic acid, methacrylic acid salt, itaconic acid, itaconic acid salt, maleic acid, maleic acid salt, N-vinyl pyrrolidone, acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, 2-methylacrylamide, N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, and N-hydroxypropylacrylamide;

[0022] B. the aromatic aliphatic nonionic emulsifier and / or aliphatic nonionic emulsifier comprises one or more of ethoxylated alkylphenol compounds, alkyl alcohol ethoxylates, homopolymers and copolymers of ethylene oxide and propylene oxide;

[0023] C. the anionic emulsifier comprises one or more of alkali metal salts and / or ammonium salts of alkyl sulfates, alkali metal salts and / or ammonium salts of sulfuric acid monoesters of ethoxylated alkanols or ethoxylated alkylphenols, and alkali metal salts and / or ammonium salts of alkyl aryl sulfonic acids of alkyl sulfonic acids;

[0024] D. the cationic emulsifier comprises a quaternary ammonium salt;

[0025] E. The zwitterionic surfactant includes a quaternary ammonium group, -COO - Base or -SO3 - Base compound.

[0026] Optionally, the lithium-ion battery binder satisfies at least one of the following conditions;

[0027] A. the ethoxylated alkylphenol compound has an alkyl number of 4-10 and an EO value of 3-50;

[0028] B. the alkyl number of the alkyl alcohol ethoxylate is 8-36, and the EO value is 3-100;

[0029] C. The zwitterionic surfactant includes one or more of betaine compounds, coconut oil alkyl dimethyl ammonium glycinate, N-acylaminopropyl-N,N-dimethylammonium glycinate, coconut oil acylaminopropyl dimethyl ammonium glycinate, 2-alkyl-3-carboxymethyl-3-hydroxyethyl imidazoline, and coconut oil acylaminoethyl hydroxyethyl carboxymethyl glycinate.

[0030] The second aspect of the present application provides a method for preparing the lithium ion battery binder, comprising:

[0031] Under a protective atmosphere, a hydrophobic monomer, a functional monomer, a reactive surfactant, a non-reactive surfactant, a crosslinking agent, a chain transfer agent, a portion of a hydrophilic monomer and a portion of water are first mixed to obtain a pre-emulsion;

[0032] A part of the initiator and the pre-emulsion are mixed for a second time, and a copolymer emulsion is obtained by a first polymerization;

[0033] The lipophilic monomer and the remaining hydrophilic monomer are mixed for a third time to obtain a monomer mixture;

[0034] The monomer mixture, the copolymer emulsion, and the remaining initiator are mixed for the fourth time, and polymerized for the second time to obtain a mixed solution;

[0035] The mixed solution, the alkaline neutralizer and the remaining water are mixed in a fifth step to obtain a lithium ion battery binder.

[0036] Optionally, the preparation method of the lithium ion battery binder meets at least one of the following conditions:

[0037] A. The protective gas in the protective atmosphere includes nitrogen;

[0038] B. The raw materials for preparing the copolymer emulsion include, by parts:

[0039] The hydrophilic monomer is 0-45 parts, the hydrophobic monomer is 75-90 parts, the functional monomer is 0.2-8 parts, the reactive surfactant is 1-13 parts, the non-reactive surfactant is 0.5-8 parts, the cross-linking agent is 0.1-5.0 parts, the initiator is 0.05-2.0 parts, the chain transfer agent is 0.1-2.0 parts, and the water is 7-150 parts;

[0040] C. The raw materials in the monomer mixture include, by weight:

[0041] 25-27 parts of hydrophilic monomer, 3-5 parts of lipophilic monomer;

[0042] D. the mass ratio of the remaining initiator to the monomer mixture is 0.01-5:100;

[0043] E. The mass concentration of the monomers in the monomer mixture is 10%-40%;

[0044] F. the total mass of monomers in the monomer mixture accounts for 10% to 200% of the total mass of monomers in the copolymer emulsion;

[0045] G. the endpoint pH value of the fifth mixing is 6-12;

[0046] H. The end point solid content of the fifth mixing is 4%-10%;

[0047] I. The method for preparing the copolymer emulsion also includes:

[0048] Under a protective atmosphere, the hydrophobic monomer, the functional monomer, the non-reactive surfactant, the crosslinking agent, the chain transfer agent, a portion of the hydrophilic monomer, a portion of the reactive surfactant and a portion of the water are mixed for a fifth time to obtain a first pre-emulsion;

[0049] The first pre-emulsion, a part of the initiator, and the remaining reactive surfactant are mixed for the sixth time to obtain a first polymerization product.

[0050] Optionally, the preparation method of the lithium ion battery binder meets at least one of the following conditions:

[0051] A. The heating rate of the first mixture is 1°C / min-3°C / min, the heating end point temperature is 60°C-90°C, and the holding time is 30min-60min;

[0052] B. The second mixing time is 220min-570min;

[0053] C. The second mixing comprises:

[0054] Part of the initiator includes a first initiator and a second initiator;

[0055] The first initiator and the second initiator are respectively configured into the first initiator aqueous solution and the second initiator aqueous solution;

[0056] After subjecting the first initiator aqueous solution and the pre-emulsion to a first polymerization, the pre-emulsion and the second initiator aqueous solution are subjected to a second polymerization to obtain the copolymer emulsion;

[0057] D. the mass ratio of the remaining initiator to the monomer mixture is 0.1-1:100;

[0058] E. The monomer mass concentration in the monomer mixture is 25%-35%;

[0059] F. the total mass of monomers in the monomer mixture accounts for 50% to 90% of the total mass of monomers in the copolymer emulsion;

[0060] G. The remaining initiator is configured into a remaining initiator aqueous solution before use, and the mass concentration of the remaining initiator aqueous solution is 5%-15%;

[0061] H. The temperature of the fourth mixing is 50°C-95°C, and the time is 1h-10h;

[0062] I. the endpoint pH value of the fifth mixing is 7-9;

[0063] J. The end point solid content of the fifth mixing is 5%-7%;

[0064] K. the number of parts of the reactive surfactant for the fifth mixing is 0.5 parts to 10 parts;

[0065] L. The amount of the reactive surfactant used in the sixth mixing is 0.5 to 3 parts.

[0066] Optionally, the preparation method of the lithium ion battery binder meets at least one of the following conditions:

[0067] A. the concentration of the first initiator aqueous solution is 1Wt%-20Wt%;

[0068] B. the concentration of the second initiator aqueous solution is 1Wt%-15Wt%;

[0069] C. The mass ratio of the first initiator to the second initiator is 0.5:1-1:2;

[0070] D. The temperature of the fourth mixing is 68°C-78°C, and the time is 2h-4h.

[0071] The third aspect of the present application provides a lithium-ion battery, comprising the lithium-ion battery binder or the lithium-ion battery binder prepared by the preparation method of the lithium-ion battery binder, and a silicon-carbon negative electrode material.

[0072] A fourth aspect of the present application provides an electrical device, including the lithium-ion battery.

[0073] Compared with the prior art, the beneficial effects of this application include:

[0074] The lithium-ion battery binder provided in the present application has a core-whisker structure. The flexible core can provide a buffering effect on the stress caused by the volume expansion change on the particle surface, while the rigid whiskers prepared with hydrophilic chain segments provide a strong bonding force between micron silicon particles, making it difficult for the active material to desorb from the collector during circulation. The lithium-ion battery binder can improve the cycle performance and inhibit expansion.

[0075] The preparation method of the lithium ion battery binder provided in the present application comprises the following steps: firstly, a copolymer emulsion (white emulsion) is obtained by a first polymerization (emulsion polymerization), wherein the copolymer emulsion is mainly composed of a hydrophobic monomer to synthesize a flexible inner core with high flexibility, low surface tension and affinity to silicon-carbon particles; and then a hydrophilic high-strength tentacle structure is continuously grown on the surface of the flexible inner core in an in-situ growth manner by a second polymerization (in-situ polymerization), because a monomer mixture obtained by mixing an oleophilic monomer and a hydrophilic monomer will first be captured by the colloid particles of the copolymer emulsion, and the monomer mixture is free on the surface of the latex particles, thereby forming the core-whisker structure; the scheme has low raw material cost, controls production cost on the basis of innovative process, is easy to scale up, has simple and easy-to-control preparation process, is low-cost, environmentally friendly and pollution-free, and has prospects for industrial application.

[0076] The lithium-ion battery provided in the present application, specifically a lithium-ion battery using the present binder, can improve the cycle.

[0077] The electrical equipment provided by the present application, specifically the electrical equipment using the adhesive in the present application, can improve the durability of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0079] Figure 1 Schematic diagram of the lithium-ion battery binder and core whisker structure provided in this application;

[0080] Figure 2 This is a scanning electron microscope image of the lithium ion battery binder provided in Example 1. DETAILED DESCRIPTION

[0081] As used herein:

[0082] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0083] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0084] In these examples, parts and percentages are by mass unless otherwise indicated.

[0085] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0086] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0087] The first aspect of the present application provides a lithium ion battery binder, the raw materials of which include:

[0088] Hydrophilic monomer, hydrophobic monomer, functional monomer, reactive surfactant, non-reactive surfactant, initiator, crosslinking agent, chain transfer agent, lipophilic monomer, alkaline neutralizer and water;

[0089] The lithium ion battery binder is a core-whisker structure.

[0090] It should be noted that the structure is mainly composed of two parts: first, the inner core is obtained by emulsion polymerization with hydrophobic monomers as the main component, and the main monomer composition of the inner core is the polymerization of hydrophobic monomers and a small amount of hydrophilic monomers. In the structural design of the inner core, by designing different types and proportions of hydrophobic monomers, polymers with different glass transition temperatures can be obtained to control the mechanical properties of the binder, which can better adapt to the expansion of micron silicon particles with different structures, and through the combined application of reactive emulsifiers and non-reactive emulsifiers, the distribution structure of the surface emulsifier of the polymer latex particles in the reaction process can be regulated, thereby obtaining an intermediate product that is beneficial to the core-whisker structure; the second is the whisker structure, which is mainly composed of hydrophilic monomers, with a small amount of other monomers as auxiliary. Other monomers can greatly improve the strength of the whisker structure while maintaining hydrophilicity, and the improvement of the strength of the whisker structure can make the binder with a core-whisker structure have a stronger ability to effectively bond different micron silicon particles.

[0091] It should be noted that the core-whisker structure can be understood as a flexible core with the outermost layer connected to one end of many long chains, thus forming a structure in which a core is connected to multiple long chains. Figure 1 shown.

[0092] In some embodiments, the lithium ion battery binder satisfies at least one of the following conditions:

[0093] A. the hydrophilic monomer comprises a compound containing a carboxyl group and / or a sulfonic acid group;

[0094] It should be noted that the hydrophilic monomer is based on structural design reasons, and only by selecting monomers and polymers with different solubility in the solvent can the concept of the core-whisker structure be realized.

[0095] B. the hydrophobic monomer comprises one or more of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, hexyl acrylate, hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, acrylonitrile, methacrylonitrile, glycidyl acrylate, glycidyl methacrylate, maleic anhydride, allyl glycidyl ether, glycidyl ethyl acrylate, dimethyl-m-isopropenyl-benzyl isocyanate, and methylene succinic anhydride;

[0096] It should be noted that the selection of this type of hydrophobic monomer is based on the reason that it has a better expansion inhibition effect on micron silicon particles.

[0097] C. the functional monomers include lower alkyl methacrylate, hydroxyalkyl (meth)acrylate, polyethylene glycol allyl ether, polypropylene glycol vinyl ether, polypropylene glycol allyl ether, polyethylene glycol methacrylate, polypropylene glycol methacrylate, C8-C30 alkyl methacrylate, dodecyl acrylate, lauric methacrylate, hexadecyl acrylate, octadecyl acrylate, behenyl acrylate, vinyl dodecanoate, vinyl hexadecanoate, vinyl octadecanoate, vinyl behenate, dodecyl vinyl ether, hexadecyl vinyl ether, octadecyl vinyl ether, behenyl vinyl ether, polyethylene glycol methacrylate, lauryl acrylate, polyethylene glycol methacrylate, octadecyl acrylate, one or more;

[0098] It should be noted that the functional monomer is based on the effective regulation of the mechanical properties of the core part of the binder.

[0099] D. the reactive surfactant comprises one or more of allyloxy nonylphenol polyoxyethylene ether, allyl ether sulfonate, acrylamide sulfonate, maleic acid derivative, sodium allyl alkyl succinate sulfonate, allyl polyether, acrylic acid polyether phosphate, methacrylic acid polyether phosphate, alcohol ether phosphate containing double bonds, methacrylamide isopropyl sulfonic acid, methacrylamide isopropyl sulfonate, alkyl alcohol ether sulfate containing allyl, alkyl alcohol ether sulfate containing double bonds, dialkyl sulfosuccinate containing double bonds, vinyl sulfonate, sodium 1-propyleneoxy-2-hydroxypropane sulfonate, alkylpropylene phenoxy polyether sulfate, allyl polyether phosphate, and polyether ammonium phosphate containing double bonds;

[0100] It should be noted that reactive surfactants can better control the structure of emulsion particles.

[0101] E. The non-reactive surfactant includes one or more of aromatic aliphatic nonionic emulsifiers, aliphatic nonionic emulsifiers, anionic emulsifiers, cationic emulsifiers, and zwitterionic surfactants;

[0102] F. the initiator comprises one or more of ammonium persulfate, potassium persulfate, sodium persulfate, benzoyl peroxide, dodecyl peroxide, lauroyl peroxide, dicumyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, azobisisobutyronitrile, azobisisoheptylnitrile, tert-butyl hydroperoxide, sucrose, daunolide, sodium pyrosulfite, N,N-dimethylaniline, sodium bisulfite, tartaric acid, daunolide, ferrous sulfate, N,N-diethylaniline, ferrous pyrophosphate, silver nitrate, mercaptan, cumene hydroperoxide, ferrous chloride, tetraethyleneimine, and vitamin C;

[0103] It is important to note that the non-reactive surfactant can maintain the concentration of the emulsifier during the emulsion polymerization process.

[0104] G. the cross-linking agent includes one or more of butadiene, isoprene, divinylbenzene, dicyclopentadiene, divinylnaphthalene, N,N-methylenebisacrylamide, divinyl phthalate, sucrose polyallyl ether, pentaerythritol diallyl ether, pentaerythritol triallyl ether, pentaerythritol tetraallyl ether, trimethylolpropane diallyl ether, trimethylolpropane triallyl, and polyethyleneimine;

[0105] It should be noted that the cross-linking agent is based on the fact that the effect suitable for micron silicon bonding and expansion inhibition can be obtained through different types and ratios of cross-linking agents;

[0106] In some embodiments, the number of allyl groups in the sucrose polyallyl ether is 2-8;

[0107] H. the chain transfer agent comprises n-dodecyl mercaptan;

[0108] It should be noted that chain transfer agents can reasonably regulate molecular weight.

[0109] I. The lipophilic monomer comprises one or more of acrylonitrile, methacrylonitrile, styrene, methyl acrylate, ethyl acrylate, n-butyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, isobornyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, vinyl acetate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and glycidyl methacrylate;

[0110] J. The alkaline neutralizing agent includes one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium carbonate, potassium hydroxide, calcium carbonate, calcium hydroxide, lithium carbonate, lithium bicarbonate, lithium hydroxide, and ammonia water.

[0111] It should be noted that the alkaline neutralizer is used to adjust the pH value of the binder. Too high a pH value will cause the material to degrade, while too low a pH value will reduce the initial efficiency of the lithium battery.

[0112] Optionally, the lithium-ion battery binder satisfies at least one of the following conditions;

[0113] A. the hydrophilic monomer comprises one or more of acrylic acid, acrylic acid salt, methacrylic acid, methacrylic acid salt, allyloxyhydroxypropyl sulfonic acid, allyloxyhydroxypropyl sulfonic acid salt, vinyl sulfonic acid, vinyl sulfonic acid salt, 2-acrylamide-2-methylpropane sulfonic acid, propylene sulfonic acid, propylene sulfonic acid salt, methacrylic acid, methacrylic acid salt, itaconic acid, itaconic acid salt, maleic acid, maleic acid salt, N-vinyl pyrrolidone, acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, 2-methylacrylamide, N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, and N-hydroxypropylacrylamide;

[0114] B. the aromatic aliphatic nonionic emulsifier and / or aliphatic nonionic emulsifier comprises one or more of ethoxylated alkylphenol compounds, alkyl alcohol ethoxylates, homopolymers and copolymers of ethylene oxide and propylene oxide;

[0115] It is to be noted that copolymers of ethylene oxide and propylene oxide contain alkylene oxide units copolymerized in random distribution or in the form of blocks;

[0116] In some embodiments, the alkyl alcohol ethoxylate comprises a long chain alkyl alcohol ethoxylate, wherein the alkyl number is 8-30 and the average degree of ethoxylation is 5-100;

[0117] C. the anionic emulsifier comprises one or more of alkali metal salts and / or ammonium salts of alkyl sulfates, alkali metal salts and / or ammonium salts of sulfuric acid monoesters of ethoxylated alkanols or ethoxylated alkylphenols, and alkali metal salts and / or ammonium salts of alkyl aryl sulfonic acids of alkyl sulfonic acids;

[0118] In some embodiments, the number of alkyl groups in the alkali metal salt and / or ammonium salt of alkyl sulfate is 8-22;

[0119] In some embodiments, the alkyl number of the ethoxylated alkanol in the alkali metal salt and / or ammonium salt of the sulfuric acid monoester of the ethoxylated alkanol or ethoxylated alkylphenol is 12-18 and the EO level is 2-50; the alkyl number of the ethoxylated alkylphenol is 4-9 and the EO level is 3-50;

[0120] In some embodiments, the alkyl number of the alkyl sulfonic acid in the alkali metal salt and / or ammonium salt of the alkyl aryl sulfonic acid of the alkyl sulfonic acid is 12-18, and the alkyl number of the alkyl aryl sulfonic acid is 9-18;

[0121] D. the cationic emulsifier comprises a quaternary ammonium salt;

[0122] In some embodiments, the cationic emulsifier includes one or more of trimethyl hexadecyl ammonium chloride, methyl trioctyl ammonium chloride, benzyl triethyl ammonium chloride, and quaternary ammonium compounds of N-C6-C20 alkyl pyridine, N-C6-C20 alkyl morpholine, and N-C6-C20 alkyl imidazole;

[0123] E. The zwitterionic surfactant includes a quaternary ammonium group, -COO - Base or -SO3 - Base compound.

[0124] In some embodiments, the lithium ion battery binder satisfies at least one of the following conditions:

[0125] A. the ethoxylated alkylphenol compound has an alkyl number of 4-10 and an EO value of 3-50;

[0126] Optionally, the number of alkyl groups of the ethoxylated alkylphenol compound may be 4, 6, 8, 10 or any value between 4 and 10, and the EO value may be 3, 5, 10, 20, 30, 40, 50 or any value between 3 and 50;

[0127] B. the alkyl number of the alkyl alcohol ethoxylate is 8-36, and the EO value is 3-100;

[0128] Optionally, the number of alkyl groups of the alkyl alcohol ethoxylate may be 8, 10, 20, 30, 36 or any value between 8 and 36, and the EO value may be 3, 10, 50, 100 or any value between 3 and 100;

[0129] C. The zwitterionic surfactant includes one or more of betaine compounds, coconut oil alkyl dimethyl ammonium glycinate, N-acylaminopropyl-N,N-dimethylammonium glycinate, coconut oil acylaminopropyl dimethyl ammonium glycinate, 2-alkyl-3-carboxymethyl-3-hydroxyethyl imidazoline, and coconut oil acylaminoethyl hydroxyethyl carboxymethyl glycinate.

[0130] It should be noted that the number of carbon atoms in the alkyl or acyl group of the zwitterionic surfactant is 8-18.

[0131] The second aspect of the present application provides a method for preparing the lithium ion battery binder, comprising:

[0132] Under a protective atmosphere, a hydrophobic monomer, a functional monomer, a reactive surfactant, a non-reactive surfactant, a crosslinking agent, a chain transfer agent, a portion of a hydrophilic monomer and a portion of water are first mixed to obtain a pre-emulsion;

[0133] It should be noted that the negative effect of oxygen inhibiting the reaction can be reduced under a protective atmosphere;

[0134] A part of the initiator and the pre-emulsion are mixed for a second time, and a copolymer emulsion is obtained by a first polymerization;

[0135] The lipophilic monomer and the remaining hydrophilic monomer are mixed for a third time to obtain a monomer mixture;

[0136] The monomer mixture, the copolymer emulsion, and the remaining initiator are mixed for the fourth time, and polymerized for the second time to obtain a mixed solution;

[0137] The mixed solution, the alkaline neutralizer and the remaining water are mixed in a fifth step to obtain a lithium ion battery binder.

[0138] In some embodiments, the method for preparing the lithium ion battery binder satisfies at least one of the following conditions:

[0139] A. The protective gas in the protective atmosphere includes nitrogen;

[0140] B. The raw materials for preparing the copolymer emulsion include, by parts:

[0141] The hydrophilic monomer is 0-45 parts, the hydrophobic monomer is 70-90 parts, the functional monomer is 0.2-8 parts, the reactive surfactant is 1-13 parts, the non-reactive surfactant is 0.5-8 parts, the cross-linking agent is 0.1-5.0 parts, the initiator is 0.05-2.0 parts, the chain transfer agent is 0.1-2.0 parts, and the water is 7-150 parts;

[0142] Optionally, the raw materials of the copolymer emulsion are calculated by parts, the hydrophilic monomer can be 0 parts, 5 parts, 15 parts, 25 parts, 35 parts, 45 parts or any value between 0 parts and 45 parts, the hydrophobic monomer can be 70 parts, 80 parts, 90 parts or any value between 70 parts and 90 parts, the functional monomer can be 0.2 parts, 1 parts, 2 parts, 4 parts, 6 parts, 8 parts or any value between 0.2 parts and 8 parts, the reactive surfactant can be 1 part, 2 parts, 4 parts, 6 parts, 8 parts, 10 parts, 13 parts or any value between 1 part and 13 parts, and the non-reactive surfactant can be 0.5 The amount of water can be 7 parts, 10 parts, 50 parts, 100 parts, 150 parts or any value between 7 parts and 150 parts; the amount of crosslinking agent can be 0.1 parts, 0.5 parts, 1 parts, 2 parts, 4 parts, 5.0 parts or any value between 0.1 parts and 5.0 parts; the amount of initiator can be 0.05 parts, 0.5 parts, 1 parts, 2 parts or any value between 0.05 parts and 2.0 parts; the amount of chain transfer agent can be 0.1 parts, 0.5 parts, 1 parts, 2 parts or any value between 0.1 parts and 2.0 parts; and the amount of water can be 7 parts, 10 parts, 50 parts, 100 parts, 150 parts or any value between 7 parts and 150 parts;

[0143] C. The raw materials in the monomer mixture include, by weight:

[0144] 25-27 parts of hydrophilic monomer, 3-5 parts of lipophilic monomer;

[0145] Optionally, the raw materials in the monomer mixture may be 25 parts, 26 parts, 27 parts or any value between 25 parts and 27 parts in terms of weight, and the lipophilic monomer may be 3 parts, 4 parts, 5 parts or any value between 3 parts and 5 parts in terms of weight;

[0146] D. the mass ratio of the remaining initiator to the monomer mixture is 0.01-5:100;

[0147] Optionally, the mass ratio of the remaining initiator to the monomer mixture may be 0.01:100, 0.1:100, 1:100, 2:100, 3:100, 4:100, 5:100 or any value between 0.01 and 5:100;

[0148] E. The mass concentration of the monomers in the monomer mixture is 10%-40%;

[0149] Optionally, the mass concentration of the monomer in the monomer mixture may be 10%, 20%, 30%, 40% or any value between 10% and 40%;

[0150] F. the total mass of monomers in the monomer mixture accounts for 10% to 200% of the total mass of monomers in the copolymer emulsion;

[0151] G. the endpoint pH value of the fifth mixing is 6-12;

[0152] Optionally, the endpoint pH value of the fifth mixing may be 6, 8, 10, 12 or any value between 6 and 12;

[0153] It should be noted that too high a pH value will cause the material to degrade, while too low a pH value will reduce the initial efficiency of the lithium battery.

[0154] H. The end point solid content of the fifth mixing is 4%-10%;

[0155] Optionally, the endpoint solid content of the fifth mixing may be 4%, 6%, 8%, 10% or any value between 4% and 10%;

[0156] It should be noted that when the end point solid content of the fifth mixing is 4%-10%, this viscosity range is more suitable for transportation and processing.

[0157] I. The method for preparing the copolymer emulsion also includes:

[0158] Under a protective atmosphere, the hydrophobic monomer, the functional monomer, the non-reactive surfactant, the crosslinking agent, the chain transfer agent, a portion of the hydrophilic monomer, a portion of the reactive surfactant and a portion of the water are mixed for a fifth time to obtain a first pre-emulsion;

[0159] The first pre-emulsion, a part of the initiator, and the remaining reactive surfactant are mixed for the sixth time to obtain a first polymerization product.

[0160] It should be noted that adding the reactive surfactant in two steps can better control the distribution of the emulsifier on the surface and inside the emulsion particles before and during the reaction.

[0161] In some embodiments, the method for preparing the lithium ion battery binder satisfies at least one of the following conditions:

[0162] A. The heating rate of the first mixture is 1°C / min-3°C / min, the heating end point temperature is 60°C-90°C, and the holding time is 30min-60min;

[0163] Optionally, the heating rate of the first mixing can be 1°C / min, 2°C / min, 3°C / min or any value between 1°C / min-3°C / min, the heating end point temperature can be 60°C, 70°C, 80°C, 90°C or any value between 60°C-90°C, and the insulation time can be 30min, 40min, 50min, 60min or any value between 30min-60min;

[0164] B. The second mixing time is 220min-570min;

[0165] Optionally, the second mixing time can be 220 min, 250 min, 300 min, 350 min, 400 min, 450 min, 500 min, 570 min or any value between 220 min and 570 min;

[0166] C. The second mixing comprises:

[0167] Part of the initiator includes a first initiator and a second initiator;

[0168] The first initiator and the second initiator are respectively configured into the first initiator aqueous solution and the second initiator aqueous solution;

[0169] After subjecting the first initiator aqueous solution and the pre-emulsion to a first polymerization, the pre-emulsion and the second initiator aqueous solution are subjected to a second polymerization to obtain the copolymer emulsion;

[0170] It should be noted that part of the initiator is added in two steps, which can better control the distribution of the emulsifier on the surface and inside the emulsion particles before and during the reaction.

[0171] D. the mass ratio of the remaining initiator to the monomer mixture is 0.1-1:100;

[0172] Optionally, the mass ratio of the remaining initiator to the monomer mixture may be 0.1:100, 0.5:100, 1:100 or any value between 0.1 and 1:100;

[0173] E. The monomer mass concentration in the monomer mixture is 25%-35%;

[0174] Optionally, the mass concentration of the monomer in the monomer mixture may be 25%, 30%, 35% or any value between 25% and 35%;

[0175] F. the total mass of monomers in the monomer mixture accounts for 50% to 90% of the total mass of monomers in the copolymer emulsion;

[0176] Optionally, the total mass of monomers in the monomer mixture may account for 50%, 60%, 70%, 80%, 90% or any value between 50% and 90% of the total mass of monomers in the copolymer emulsion;

[0177] G. The remaining initiator is configured into a remaining initiator aqueous solution before use, and the mass concentration of the remaining initiator aqueous solution is 5%-15%;

[0178] Optionally, the remaining initiator is configured into a remaining initiator aqueous solution before use, and the mass concentration of the remaining initiator aqueous solution may be 5%, 10%, 15% or any value between 5% and 15%;

[0179] H. The temperature of the fourth mixing is 50°C-95°C, and the time is 1h-10h;

[0180] Optionally, the temperature of the fourth mixing may be 50°C, 60°C, 70°C, 80°C, 90°C, 95°C or any value between 50°C and 95°C, and the time may be 1h, 2h, 4h, 6h, 8h, 10h or any value between 1h and 10h;

[0181] I. the endpoint pH value of the fifth mixing is 7-9;

[0182] Optionally, the endpoint pH value of the fifth mixing may be 7, 8, 9 or any value between 7 and 9;

[0183] J. The end point solid content of the fifth mixing is 5%-7%;

[0184] Optionally, the endpoint solid content of the fifth mixing may be 5%, 6%, 7% or any value between 5% and 7%;

[0185] K. the number of parts of the reactive surfactant for the fifth mixing is 0.5 parts to 10 parts;

[0186] Optionally, the number of parts of the reactive surfactant for the fifth mixing may be 0.5 parts, 1 parts, 5 parts, 10 parts, or any value between 0.5 parts and 10 parts;

[0187] L. The amount of the reactive surfactant used in the sixth mixing is 0.5 to 3 parts.

[0188] Optionally, the number of parts of the reactive surfactant used in the sixth mixing may be 0.5 parts, 1 parts, 2 parts, 3 parts, or any value between 0.5 parts and 3 parts.

[0189] In some embodiments, the method for preparing the lithium ion battery binder satisfies at least one of the following conditions:

[0190] A. the concentration of the first initiator aqueous solution is 1Wt%-20Wt%;

[0191] Optionally, the concentration of the first initiator aqueous solution may be 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt% or any value between 1 wt% and 20 wt%;

[0192] B. the concentration of the second initiator aqueous solution is 1Wt%-15Wt%;

[0193] Optionally, the concentration of the second initiator aqueous solution may be 1 wt%, 5 wt%, 10 wt%, 15 wt%, or any value between 1 wt% and 15 wt%;

[0194] C. The mass ratio of the first initiator to the second initiator is 0.5:1-1:2;

[0195] Optionally, the mass ratio of the first initiator to the second initiator may be 0.5:1, 1:1, 0.5:2 or any value between 0.5:1 and 1:2;

[0196] D. The temperature of the fourth mixing is 68°C-78°C, and the time is 2h-4h.

[0197] Optionally, the temperature of the fourth mixing may be 68° C., 70° C., 75° C., 78° C. or any value between 68° C. and 78° C., and the time may be 2 h, 3 h, 4 h or any value between 2 h and 4 h.

[0198] It should be noted that the silicon-carbon negative electrode material of micron silicon in the prior art suffers from problems such as reversible capacity decay and increased expansion due to the failure of binder bonding, shedding of active substances, and breakage of micron silicon particles caused by huge volume expansion and contraction during the cycle. Based on this technical dilemma, the third aspect of the present application provides a lithium-ion battery, including the lithium-ion battery binder or the lithium-ion battery binder prepared by the preparation method of the lithium-ion battery binder, and the silicon-carbon negative electrode material.

[0199] In some embodiments, the silicon in the silicon-carbon negative electrode material is micron silicon.

[0200] It should be noted that the core-whisker structure of the binder provided in this application is particularly suitable for the micron silicon silicon carbon negative electrode material system that expands more significantly during the charge and discharge process; the mainstream lithium-ion battery negative electrode materials are mainly graphite, nano silicon carbon and nano silicon oxygen, and the general range of their full charge expansion is 5-10%, 20-40%, and 15-35%, respectively. Micron silicon can expand by 50-150% because its silicon particles are several orders of magnitude higher than nano silicon, so it is more necessary to match it with a binder that is both soft and hard to achieve better performance. The micron silicon binder with a core-whisker structure in this application has a flexible core and rigid tentacles (i.e., whiskers). The flexible core is bonded to the surface of the micron silicon particles. Its flexibility allows it to maintain the bonding effect of the surface in a strong expansion stress, and the rigid whiskers can tightly bond different micron silicon particles together, so that the active material shedding phenomenon caused by the volume change stress generated by the expansion change of the particles during the cycle is greatly improved, thereby improving the cycle.

[0201] In some embodiments, the lithium-ion battery further includes a positive electrode active material, and the positive electrode active material includes a single crystal ternary positive electrode material.

[0202] A fourth aspect of the present application provides an electrical device, including the lithium-ion battery.

[0203] It should be noted that electrical equipment includes but is not limited to one or more of electric vehicles, electric bicycles, smart home devices, robots, heavy trucks, ships and energy storage systems.

[0204] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0205] Example 1

[0206] In a first aspect, the present embodiment provides a lithium ion battery binder, the raw materials of which include:

[0207] Hydrophilic monomer, hydrophobic monomer, functional monomer, reactive surfactant, non-reactive surfactant, initiator, crosslinking agent, chain transfer agent, lipophilic monomer, alkaline neutralizer and water;

[0208] The lithium ion battery binder is a core-whisker structure.

[0209] A second aspect of the present embodiment provides a method for preparing a lithium ion battery binder, comprising:

[0210] S1: Dissolve 2.0 parts of M-30S, a reactive surfactant containing a double bond, and 1.0 parts of trimethyl hexadecyl ammonium chloride, a non-reactive surfactant, in 4.5 parts of deionized water, and add 10 parts of acrylic acid, 10 parts of acrylamide, 40 parts of butyl acrylate, 30 parts of styrene, 6 parts of dodecyl acrylate, 2.0 parts of divinylbenzene, a crosslinking agent, and 0.5 parts of n-dodecyl mercaptan, a chain transfer agent, in sequence; mix for 45 minutes at a speed of 300 rpm, during which nitrogen is introduced at a flow rate of 150 mL / min, and the temperature is raised to 80°C at a heating rate of 2°C / min, and kept warm for 45 minutes to form a pre-emulsion;

[0211] S2: Dissolve 2 parts of reactive surfactant allyloxy nonylphenol polyoxyethylene ether in 3 parts of deionized water by weight, rotate at 300 rpm, introduce N2 gas at a flow rate of 150 mL / min, heat to 90°C at a heating rate of 1°C / min, and keep warm for 30 minutes to obtain a reactive surfactant solution;

[0212] S3: 0.1 part of initiator ammonium persulfate is added to deionized water to prepare a first initiator aqueous solution with a concentration of 10 wt%, and the initiator solution and the pre-emulsion after heat preservation are continuously added dropwise to the reactive surfactant solution at the same time. The addition is completed after 100 minutes, and the solution is kept warm for 0.5 hours to obtain a copolymer seed emulsion;

[0213] S4: 2.0 parts of initiator ammonium persulfate are used to prepare a second initiator aqueous solution with deionized water, the concentration of which is 10 wt%, and the second initiator aqueous solution is added dropwise to the copolymer seed emulsion for 120 min. After the addition is completed, the mixture is kept warm for 2 h to obtain an acrylic acid (ester) copolymer emulsion;

[0214] S5: stirring a mixture of 25 parts of a hydrophilic monomer acrylic acid and 5 parts of a lipophilic monomer acrylonitrile to obtain a monomer mixture, wherein the monomer mass concentration of the monomer mixture is 30%, and the total mass of the monomer mixture accounts for 30% of the total mass of the monomers in the copolymer emulsion;

[0215] S6: 0.02 parts of initiator sodium persulfate and water are mixed to prepare an initiator aqueous solution with a concentration of 10%;

[0216] S7: adding the monomer mixture and the initiator aqueous solution prepared in S6 to the acrylic acid (ester) copolymer emulsion by two dropping pumps respectively, the dropping time is 5 hours, and the temperature is 80° C.;

[0217] S8: After the dropwise addition is completed, the mixture is kept warm for 3 hours, and the pH value is neutralized to 8.0 with an alkaline neutralizer of 10% sodium hydroxide aqueous solution, and then deionized water is added to adjust the solid content to 10%, thereby obtaining the lithium ion battery binder.

[0218] The scanning electron microscopy of the lithium-ion battery binder is as follows Figure 2 As shown in the figure, it can be clearly seen that the flexible core and the external whiskers with different hydrophilicity levels, the part with dense whisker structure is the semi-permeable part connected to the core, and the part with sparse whisker structure is the irregular tentacles vaguely visible outside the semi-permeable part; the test method is: dilute the emulsion to a mass concentration of 0.1%, dip-coat it on the film-carrying copper mesh, dye it with phosphomolybdic acid, and after natural drying, use the FEI Tecnai G2 F20 S-TWIN transmission electron microscope (TEM) of FEI Company of the United States to observe its morphology.

[0219] A third aspect of the present embodiment provides a lithium-ion battery, wherein the above-mentioned lithium-ion battery binder, micron silicon-carbon negative electrode material, conductive carbon black, SWCNT aqueous dispersion slurry and sodium carboxymethyl cellulose are made into a negative electrode slurry, which is then coated on a negative electrode current collector copper foil, and is made into a negative electrode pole piece through processes such as drying, rolling and cutting. The prepared negative electrode piece and a pole piece made of a five-series single crystal ternary positive electrode material are made into a soft-pack battery.

[0220] Example 2

[0221] In a first aspect, the present embodiment provides a lithium ion battery binder, the raw materials of which include:

[0222] Hydrophilic monomer, hydrophobic monomer, functional monomer, reactive surfactant, non-reactive surfactant, initiator, crosslinking agent, chain transfer agent, lipophilic monomer, alkaline neutralizer and water;

[0223] The lithium ion battery binder is a core-whisker structure.

[0224] A second aspect of the present embodiment provides a method for preparing a lithium ion battery binder, comprising:

[0225] S1: Dissolve 3.0 parts of a reactive surfactant, a double-bond-containing alkyl alcohol ether sulfate, and 1.0 parts of a non-reactive surfactant, 2-alkyl-3-carboxymethyl-3-hydroxyethyl imidazoline in 6 parts of deionized water, and sequentially add 10 parts of a hydrophilic monomer, acrylic acid, 10 parts of acrylamide, 30 parts of a hydrophobic monomer, isobutyl acrylate, 40 parts of styrene, 6 parts of a functional monomer, polyethylene glycol ester, 1.5 parts of a cross-linking agent, and 0.5 parts of a chain transfer agent, n-dodecyl mercaptan; mix at a speed of 300 rpm for 45 minutes, during which nitrogen is introduced at a flow rate of 150 mL / min, and the temperature is raised to 80°C at a heating rate of 2°C / min, and kept warm for 45 minutes to form a pre-emulsion;

[0226] S2: Dissolve 2 parts of reactive surfactant methacrylate polyether phosphate in 3 parts of deionized water, rotate at 300 rpm, introduce N2 gas at a flow rate of 150 mL / min, heat to 90°C at a heating rate of 1°C / min, and keep warm for 30 minutes to obtain a reactive surfactant solution;

[0227] S3: 0.2 parts of initiator ammonium persulfate are added to deionized water to prepare a first initiator aqueous solution with a concentration of 10 wt%, and the pre-emulsion and initiator solution after heat preservation are continuously added dropwise to the reactive surfactant solution at the same time. The addition is completed after 120 minutes, and the solution is kept warm for 2 hours to obtain an acrylic acid (ester) copolymer seed emulsion;

[0228] S4: 2.0 parts of initiator ammonium persulfate are used to prepare a second initiator aqueous solution with deionized water, the concentration of which is 10 wt%, and the second initiator aqueous solution is added dropwise to the acrylic acid (ester) copolymer seed emulsion for 120 minutes. After the addition is completed, the mixture is kept warm for 2 hours to obtain an acrylic acid (ester) copolymer emulsion;

[0229] S5: stirring a mixture of 25 parts of a hydrophilic monomer propylene sulfonic acid, 2 parts of a lipophilic monomer dimethyl-m-isopropenyl-benzyl isocyanate and 3 parts of methylene succinic anhydride to obtain a monomer mixture, wherein the monomer mass concentration of the monomer mixture is 30%, and the total mass of the monomer mixture accounts for 30% of the total mass of the monomers in the copolymer emulsion;

[0230] S6: 0.02 parts of initiator ammonium persulfate and water are mixed to prepare an initiator aqueous solution with a concentration of 10%;

[0231] S7: adding the monomer mixture and the initiator aqueous solution prepared in S6 to the acrylic acid (ester) copolymer emulsion by two dropping pumps respectively, the dropping time is 5 hours, and the temperature is 80° C.;

[0232] S8: After the dropwise addition is completed, the mixture is kept warm for 3 hours, and the pH value is neutralized to 8.0 with an alkaline neutralizer of 10% lithium hydroxide aqueous solution, and then deionized water is added to adjust the solid content to 10%, thereby obtaining the lithium ion battery binder.

[0233] A third aspect of the present embodiment provides a lithium-ion battery, wherein the above-mentioned lithium-ion battery binder, micron silicon-carbon negative electrode material, conductive carbon black, SWCNT aqueous dispersion slurry and sodium carboxymethyl cellulose are made into a negative electrode slurry, which is then coated on a negative electrode current collector copper foil, and is made into a negative electrode pole piece through processes such as drying, rolling and cutting. The prepared negative electrode piece and a pole piece made of a five-series single crystal ternary positive electrode material are made into a soft-pack battery.

[0234] Example 3

[0235] In a first aspect, the present embodiment provides a lithium ion battery binder, the raw materials of which include:

[0236] Hydrophilic monomer, hydrophobic monomer, functional monomer, reactive surfactant, non-reactive surfactant, initiator, crosslinking agent, chain transfer agent, lipophilic monomer, alkaline neutralizer and water;

[0237] The lithium ion battery binder is a core-whisker structure.

[0238] A second aspect of the present embodiment provides a method for preparing a lithium ion battery binder, comprising:

[0239] S1: Dissolve 3.0 parts of a reactive surfactant, a double-bond alkyl alcohol ether sulfate, and 1.0 parts of a non-reactive surfactant, benzyltriethylammonium chloride, in 6 parts of deionized water, and sequentially add 5 parts of a hydrophilic monomer, N-vinyl pyrrolidone, and 10 parts of itaconic acid, 35 parts of a hydrophobic monomer, maleic anhydride, and 40 parts of styrene, 6 parts of a functional monomer, methacrylate laurate, 1.5 parts of a cross-linking agent, N,N-methylenebisacrylamide, and 0.5 parts of a chain transfer agent, n-dodecyl mercaptan; mix at a speed of 300 rpm for 30 minutes, during which nitrogen is introduced at a flow rate of 150 mL / min, and the temperature is raised to 80°C at a heating rate of 2°C / min, and the temperature is kept for 45 minutes to form a pre-emulsion;

[0240] S2: Dissolve 2 parts of reactive surfactant methacrylate polyether phosphate in 3 parts of deionized water, rotate at 300 rpm, introduce N2 gas at a flow rate of 150 mL / min, heat to 90°C at a heating rate of 1°C / min, and keep warm for 30 minutes to obtain a reactive surfactant solution;

[0241] S3: 0.1 parts of initiator potassium persulfate and ferrous chloride are added to deionized water to prepare a first initiator aqueous solution with a concentration of 10 wt%. The pre-emulsion and the initiator solution are added dropwise to the reactive surfactant solution simultaneously after 120 minutes of addition. The solution is kept warm for 2 hours to obtain an acrylic acid (ester) copolymer seed emulsion.

[0242] S4: Add 1 part of each of initiator potassium persulfate and ferrous chloride to deionized water to prepare a second initiator aqueous solution with a concentration of 10 wt%, and drop the second initiator aqueous solution into the acrylic acid (ester) copolymer seed emulsion for 120 minutes. After the dropwise addition is completed, keep the temperature for 2 hours to obtain an acrylic acid (ester) copolymer emulsion;

[0243] S5: stirring a mixture of 27 parts of a hydrophilic monomer acrylamide and 3 parts of a lipophilic monomer acrylonitrile to obtain a monomer mixture, wherein the monomer mass concentration of the monomer mixture is 30%, and the total mass of the monomer mixture accounts for 30% of the total mass of the monomers in the copolymer emulsion;

[0244] S6: Mix 0.01 parts of each of potassium sulfate and ferrous chloride as initiators with water to prepare an initiator aqueous solution with a concentration of 10%;

[0245] S7: adding the monomer mixture and the initiator aqueous solution prepared in S6 to the acrylic acid (ester) copolymer emulsion by two dropping pumps respectively, the dropping time is 5 hours, and the temperature is 80° C.;

[0246] S8: After the dropwise addition is completed, the mixture is kept warm for 3 hours, and the pH value is neutralized to 8.0 with a 10% sodium carbonate aqueous solution as an alkaline neutralizer, and then deionized water is added to adjust the solid content to 10%, thereby obtaining the lithium ion battery binder.

[0247] A third aspect of the present embodiment provides a lithium-ion battery, wherein the above-mentioned lithium-ion battery binder, micron silicon-carbon negative electrode material, conductive carbon black, SWCNT aqueous dispersion slurry and sodium carboxymethyl cellulose are made into a negative electrode slurry, which is then coated on a negative electrode current collector copper foil, and is made into a negative electrode pole piece through processes such as drying, rolling and cutting. The prepared negative electrode piece and a pole piece made of a five-series single crystal ternary positive electrode material are made into a soft-pack battery.

[0248] Example 4

[0249] In a first aspect, the present embodiment provides a lithium ion battery binder, the raw materials of which include:

[0250] Hydrophilic monomer, hydrophobic monomer, functional monomer, reactive surfactant, non-reactive surfactant, initiator, crosslinking agent, chain transfer agent, lipophilic monomer, alkaline neutralizer and water;

[0251] The lithium ion battery binder is a core-whisker structure.

[0252] A second aspect of the present embodiment provides a method for preparing a lithium ion battery binder, comprising:

[0253] S1: 3.0 parts of reactive surfactant methacrylamide isopropyl sulfonate and 1.0 part of non-reactive surfactant methyl trioctyl ammonium chloride were dissolved in 6 parts of deionized water, and then 5 parts of hydrophilic monomer 2-methacrylamide and 10 parts of maleic acid, 20 parts of hydrophobic monomer isopropyl methacrylate, 25 parts of butyl acrylate, 30 parts of styrene, 6 parts of functional monomer polyethylene glycol methacrylate octadecyl ester, 2 parts of cross-linking agent divinylbenzene, and 0.5 parts of chain transfer agent n-dodecyl mercaptan were added in sequence, and the mixture was mixed at a speed of 300 rpm for 30 minutes, during which nitrogen was introduced at a flow rate of 150 mL / min, and the temperature was raised to 80°C at a heating rate of 2°C / min, and the mixture was kept warm for 45 minutes to form a pre-emulsion;

[0254] S2: Dissolve 2 parts of reactive surfactant methacrylate polyether phosphate in 3 parts of deionized water, rotate at 300 rpm, introduce N2 gas at a flow rate of 150 mL / min, heat to 90°C at a heating rate of 1°C / min, and keep warm for 30 minutes to obtain a reactive surfactant solution;

[0255] S3: 0.5 parts of initiator potassium persulfate is added to deionized water to prepare a first initiator aqueous solution with a concentration of 10 wt%, and the initiator solution and the pre-emulsion after heat preservation are continuously added dropwise to the reactive surfactant solution at the same time. The addition is completed after 120 minutes, and the solution is kept warm for 2 hours to obtain an acrylic acid (ester) copolymer seed emulsion;

[0256] S4: 2.0 parts of initiator potassium persulfate are used to prepare a second initiator aqueous solution with deionized water, the concentration of which is 10 wt%, and the second initiator aqueous solution is added dropwise to the acrylic acid (ester) copolymer seed emulsion for 120 minutes. After the addition is completed, the mixture is kept warm for 2 hours to obtain an acrylic acid (ester) copolymer emulsion;

[0257] S5: stirring a mixture of 20 parts of a hydrophilic monomer acrylamide and 5 parts of a lipophilic monomer acrylonitrile to obtain a monomer mixture, wherein the monomer mass concentration of the monomer mixture is 30%, and the total mass of the monomer mixture accounts for 30% of the total mass of the monomers in the copolymer emulsion;

[0258] S6: 0.02 parts of initiator potassium persulfate and water are mixed to prepare an initiator aqueous solution with a concentration of 10%;

[0259] S7: adding the monomer mixture and the initiator aqueous solution prepared in S6 to the acrylic acid (ester) copolymer emulsion by two dropping pumps respectively, the dropping time is 5 hours, and the temperature is 80° C.;

[0260] S8: After the dropwise addition is completed, the mixture is kept warm for 3 hours, and the pH value is neutralized to 8.0 with a 10% sodium carbonate aqueous solution as an alkaline neutralizer, and then deionized water is added to adjust the solid content to 10%, thereby obtaining the lithium ion battery binder.

[0261] A third aspect of the present embodiment provides a lithium-ion battery, wherein the above-mentioned lithium-ion battery binder, micron silicon-carbon negative electrode material, conductive carbon black, SWCNT aqueous dispersion slurry and sodium carboxymethyl cellulose are made into a negative electrode slurry, which is then coated on a negative electrode current collector copper foil, and is made into a negative electrode pole piece through processes such as drying, rolling and cutting. The prepared negative electrode piece and a pole piece made of a five-series single crystal ternary positive electrode material are made into a soft-pack battery.

[0262] Example 5

[0263] In a first aspect, the present embodiment provides a lithium ion battery binder, the raw materials of which include:

[0264] Hydrophilic monomer, hydrophobic monomer, functional monomer, reactive surfactant, non-reactive surfactant, initiator, crosslinking agent, chain transfer agent, lipophilic monomer, alkaline neutralizer and water;

[0265] The lithium ion battery binder is a core-whisker structure.

[0266] A second aspect of the present embodiment provides a method for preparing a lithium ion battery binder, comprising:

[0267] S1: 4.0 parts of reactive surfactant sodium 1-propyleneoxy 2-hydroxypropane sulfonate and 1.0 part of non-reactive surfactant ethoxylated alkanol were dissolved in 6 parts of deionized water, and then 5 parts of hydrophilic monomer 2-methacrylamide and 10 parts of acrylic acid, 20 parts of hydrophobic monomer maleic anhydride, 15 parts of butyl acrylate, 40 parts of styrene, 6 parts of functional monomer dodecyl vinyl ether, 2 parts of cross-linking agent divinylbenzene, and 0.5 parts of chain transfer agent n-dodecyl mercaptan were added in sequence, and the mixture was mixed at a speed of 300 rpm for 30 minutes, during which nitrogen was introduced at a flow rate of 150 mL / min, and the temperature was raised to 80°C at a heating rate of 2°C / min, and the mixture was kept warm for 45 minutes to form a pre-emulsion;

[0268] S2: Dissolve 2 parts of a reactive surfactant maleic acid derivative in 3 parts of deionized water, rotate at 300 rpm, introduce N2 gas at a flow rate of 150 mL / min, heat to 90°C at a heating rate of 1°C / min, and keep warm for 30 min to obtain a reactive surfactant solution;

[0269] S3: 0.5 parts of initiator potassium persulfate is added to deionized water to prepare a first initiator aqueous solution with a concentration of 10 wt%, and the initiator solution and the pre-emulsion after heat preservation are continuously added dropwise to the reactive surfactant solution at the same time. The addition is completed after 120 minutes, and the solution is kept warm for 2 hours to obtain an acrylic acid (ester) copolymer seed emulsion;

[0270] S4: 2.0 parts of initiator potassium persulfate are used to prepare a second initiator aqueous solution with deionized water, the concentration of which is 10 wt%, and the second initiator aqueous solution is added dropwise to the acrylic acid (ester) copolymer seed emulsion for 120 minutes. After the addition is completed, the mixture is kept warm for 2 hours to obtain an acrylic acid (ester) copolymer emulsion;

[0271] S5: stirring a mixture of 20 parts of a hydrophilic monomer acrylamide and 5 parts of a lipophilic monomer acrylonitrile to obtain a monomer mixture, wherein the monomer mass concentration of the monomer mixture is 30%, and the total mass of the monomer mixture accounts for 30% of the total mass of the monomers in the copolymer emulsion;

[0272] S6: 0.02 parts of initiator potassium persulfate and water are mixed to prepare an initiator aqueous solution with a concentration of 10%;

[0273] S7: adding the monomer mixture and the initiator aqueous solution prepared in S6 to the acrylic acid (ester) copolymer emulsion by two dropping pumps respectively, the dropping time is 5 hours, and the temperature is 80° C.;

[0274] S8: After the dropwise addition is completed, the mixture is kept warm for 3 hours, and the pH value is neutralized to 8.0 with a 10% sodium carbonate aqueous solution as an alkaline neutralizer, and then deionized water is added to adjust the solid content to 10%, thereby obtaining the lithium ion battery binder.

[0275] A third aspect of the present embodiment provides a lithium-ion battery, wherein the above-mentioned lithium-ion battery binder, micron silicon-carbon negative electrode material, conductive carbon black, SWCNT aqueous dispersion slurry and sodium carboxymethyl cellulose are made into a negative electrode slurry, which is then coated on a negative electrode current collector copper foil, and is made into a negative electrode pole piece through processes such as drying, rolling and cutting. The prepared negative electrode piece and a pole piece made of a five-series single crystal ternary positive electrode material are made into a soft-pack battery.

[0276] Comparative Example 1

[0277] The difference from Example 1 is that in this comparative example, all the raw materials are directly mixed.

[0278] Comparative Example 2

[0279] The difference from Example 1 is that the raw materials of the lithium ion battery binder in this comparative example do not include a chain transfer agent.

[0280] Comparative Example 3

[0281] The difference from Example 1 is that the raw material of the lithium ion battery binder in this comparative example does not include an oleophilic monomer.

[0282] Comparative Example 4

[0283] The difference from Example 1 is that the raw materials of the lithium ion battery binder in this comparative example do not include a reactive surfactant.

[0284] Comparative Example 5

[0285] The difference from Example 1 is that the raw materials of the lithium ion battery binder in this comparative example do not include a non-reactive surfactant.

[0286] Comparative Example 6

[0287] The difference from Example 1 is that the lithium ion battery binder of this comparative example does not perform step S8.

[0288] The soft-pack batteries prepared in the above examples and comparative examples were subjected to performance tests, and the specific test results are shown in Table 1.

[0289] Table 1 Performance test

[0290]

[0291]

[0292] As can be seen from Table 1, the different embodiments all use the recommended reaction monomer ratios and raw material formulations, so the performance differences between them are not large. However, among all the embodiments, Example 1 can best achieve the envisioned structure, so its electrical performance is also the best. However, due to problems in the process, Comparative Example 1 cannot produce a binder with the envisioned structure, so its electrical performance is also significantly inhibited. Comparative Example 3 has poor performance due to the lack of hydrophilic monomers that prevent the whisker structure from growing. Comparative Example 6 does not regulate the pH value, and the large amount of carboxyl groups or their anhydrides in the binder and the free acidic groups are very easy to react with lithium, resulting in a significant decrease in the first efficiency. Comparative Examples 2, 4, and 5 reduce the use of some raw materials, so the cycle performance is slightly reduced.

[0293] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A lithium ion battery binder, characterized in that: Its raw materials include: Hydrophilic monomer, hydrophobic monomer, functional monomer, reactive surfactant, non-reactive surfactant, initiator, crosslinking agent, chain transfer agent, lipophilic monomer, alkaline neutralizer and water; The lithium ion battery binder is a core-whisker structure.

2. The lithium ion battery binder according to claim 1, characterized in that: Satisfy at least one of the following conditions; A. The hydrophilic monomer includes a compound containing carboxyl groups and / or sulfonic acid groups; B. the hydrophobic monomer comprises one or more of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, hexyl acrylate, hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, acrylonitrile, methacrylonitrile, glycidyl acrylate, glycidyl methacrylate, maleic anhydride, allyl glycidyl ether, glycidyl ethyl acrylate, dimethyl-m-isopropenyl-benzyl isocyanate, and methylene succinic anhydride; C. the functional monomers include lower alkyl methacrylate, hydroxyalkyl (meth)acrylate, polyethylene glycol allyl ether, polypropylene glycol vinyl ether, polypropylene glycol allyl ether, polyethylene glycol methacrylate, polypropylene glycol methacrylate, C8-C30 alkyl methacrylate, dodecyl acrylate, lauric methacrylate, hexadecyl acrylate, octadecyl acrylate, behenyl acrylate, vinyl dodecanoate, vinyl hexadecanoate, vinyl octadecanoate, vinyl behenate, dodecyl vinyl ether, hexadecyl vinyl ether, octadecyl vinyl ether, behenyl vinyl ether, polyethylene glycol methacrylate, lauryl acrylate, polyethylene glycol methacrylate, octadecyl acrylate, one or more; D. the reactive surfactant comprises one or more of allyloxy nonylphenol polyoxyethylene ether, allyl ether sulfonate, acrylamide sulfonate, maleic acid derivative, sodium allyl alkyl succinate sulfonate, allyl polyether, acrylic acid polyether phosphate, methacrylic acid polyether phosphate, alcohol ether phosphate containing double bonds, methacrylamide isopropyl sulfonic acid, methacrylamide isopropyl sulfonate, alkyl alcohol ether sulfate containing allyl, alkyl alcohol ether sulfate containing double bonds, dialkyl sulfosuccinate containing double bonds, vinyl sulfonate, sodium 1-propyleneoxy-2-hydroxypropane sulfonate, alkylpropylene phenoxy polyether sulfate, allyl polyether phosphate, and polyether ammonium phosphate containing double bonds; E. The non-reactive surfactant includes one or more of aromatic aliphatic nonionic emulsifiers, aliphatic nonionic emulsifiers, anionic emulsifiers, cationic emulsifiers, and zwitterionic surfactants; F. the initiator comprises one or more of ammonium persulfate, potassium persulfate, sodium persulfate, benzoyl peroxide, dodecyl peroxide, lauroyl peroxide, dicumyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, azobisisobutyronitrile, azobisisoheptylnitrile, tert-butyl hydroperoxide, sucrose, daunolide, sodium pyrosulfite, N,N-dimethylaniline, sodium bisulfite, tartaric acid, daunolide, ferrous sulfate, N,N-diethylaniline, ferrous pyrophosphate, silver nitrate, mercaptan, cumene hydroperoxide, ferrous chloride, tetraethyleneimine, and vitamin C; G. the cross-linking agent includes one or more of butadiene, isoprene, divinylbenzene, dicyclopentadiene, divinylnaphthalene, N,N-methylenebisacrylamide, divinyl phthalate, sucrose polyallyl ether, pentaerythritol diallyl ether, pentaerythritol triallyl ether, pentaerythritol tetraallyl ether, trimethylolpropane diallyl ether, trimethylolpropane triallyl, and polyethyleneimine; H. the chain transfer agent comprises n-dodecyl mercaptan; I. The lipophilic monomer comprises one or more of acrylonitrile, methacrylonitrile, styrene, methyl acrylate, ethyl acrylate, n-butyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, isobornyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, vinyl acetate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and glycidyl methacrylate; J. The alkaline neutralizing agent includes one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium carbonate, potassium hydroxide, calcium carbonate, calcium hydroxide, lithium carbonate, lithium bicarbonate, lithium hydroxide, and ammonia water.

3. The lithium ion battery binder according to claim 2, characterized in that: Satisfy at least one of the following conditions; A. the hydrophilic monomer comprises one or more of acrylic acid, acrylic acid salt, methacrylic acid, methacrylic acid salt, allyloxyhydroxypropyl sulfonic acid, allyloxyhydroxypropyl sulfonic acid salt, vinyl sulfonic acid, vinyl sulfonic acid salt, 2-acrylamide-2-methylpropane sulfonic acid, propylene sulfonic acid, propylene sulfonic acid salt, methacrylic acid, methacrylic acid salt, itaconic acid, itaconic acid salt, maleic acid, maleic acid salt, N-vinyl pyrrolidone, acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, 2-methylacrylamide, N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, and N-hydroxypropylacrylamide; B. the aromatic aliphatic nonionic emulsifier and / or aliphatic nonionic emulsifier comprises one or more of ethoxylated alkylphenol compounds, alkyl alcohol ethoxylates, homopolymers and copolymers of ethylene oxide and propylene oxide; C. the anionic emulsifier comprises one or more of alkali metal salts and / or ammonium salts of alkyl sulfates, alkali metal salts and / or ammonium salts of sulfuric acid monoesters of ethoxylated alkanols or ethoxylated alkylphenols, and alkali metal salts and / or ammonium salts of alkyl aryl sulfonic acids of alkyl sulfonic acids; D. the cationic emulsifier comprises a quaternary ammonium salt; E. The zwitterionic surfactant includes a quaternary ammonium group, -COO - Base or -SO3 - Base compound.

4. The lithium ion battery binder according to claim 3, characterized in that: Satisfy at least one of the following conditions; A. the ethoxylated alkylphenol compound has an alkyl number of 4-10 and an EO value of 3-50; B. the alkyl number of the alkyl alcohol ethoxylate is 8-36, and the EO value is 3-100; C. The zwitterionic surfactant includes one or more of betaine compounds, coconut oil alkyl dimethyl ammonium glycinate, N-acylaminopropyl-N,N-dimethylammonium glycinate, coconut oil acylaminopropyl dimethyl ammonium glycinate, 2-alkyl-3-carboxymethyl-3-hydroxyethyl imidazoline, and coconut oil acylaminoethyl hydroxyethyl carboxymethyl glycinate.

5. A method for preparing a lithium ion battery binder according to any one of claims 1 to 4, characterized in that: include: Under a protective atmosphere, a hydrophobic monomer, a functional monomer, a reactive surfactant, a non-reactive surfactant, a crosslinking agent, a chain transfer agent, a portion of a hydrophilic monomer and a portion of water are first mixed to obtain a pre-emulsion; A part of the initiator and the pre-emulsion are mixed for a second time, and a copolymer emulsion is obtained by a first polymerization; The lipophilic monomer and the remaining hydrophilic monomer are mixed for a third time to obtain a monomer mixture; The monomer mixture, the copolymer emulsion, and the remaining initiator are mixed for the fourth time, and polymerized for the second time to obtain a mixed solution; The mixed solution, the alkaline neutralizer and the remaining water are mixed in a fifth step to obtain a lithium ion battery binder.

6. The method for preparing a lithium ion battery binder according to claim 5, characterized in that: At least one of the following conditions is met: A. The protective gas in the protective atmosphere includes nitrogen; B. The raw materials for preparing the copolymer emulsion include, by parts: The hydrophilic monomer is 0-45 parts, the hydrophobic monomer is 70-90 parts, the functional monomer is 0.2-8 parts, the reactive surfactant is 1-13 parts, the non-reactive surfactant is 0.5-8 parts, the cross-linking agent is 0.1-5.0 parts, the initiator is 0.05-2.0 parts, the chain transfer agent is 0.1-2.0 parts, and the water is 7-150 parts; C. The raw materials in the monomer mixture include, by weight: 25-27 parts of hydrophilic monomer, 3-5 parts of lipophilic monomer; D. the mass ratio of the remaining initiator to the monomer mixture is 0.01-5:100; E. The mass concentration of the monomers in the monomer mixture is 10%-40%; F. the total mass of monomers in the monomer mixture accounts for 10% to 200% of the total mass of monomers in the copolymer emulsion; G. the endpoint pH value of the fifth mixing is 6-12; H. The end point solid content of the fifth mixing is 4%-10%; I. The method for preparing the copolymer emulsion also includes: Under a protective atmosphere, the hydrophobic monomer, the functional monomer, the non-reactive surfactant, the crosslinking agent, the chain transfer agent, a portion of the hydrophilic monomer, a portion of the reactive surfactant and a portion of the water are mixed for a fifth time to obtain a first pre-emulsion; The first pre-emulsion, a part of the initiator, and the remaining reactive surfactant are mixed for the sixth time to obtain a first polymerization product.

7. The method for preparing a lithium ion battery binder according to claim 6, characterized in that: At least one of the following conditions is met: A. The heating rate of the first mixture is 1°C / min-3°C / min, the heating end point temperature is 60°C-90°C, and the holding time is 30min-60min; B. The second mixing time is 220min-570min; C. The second mixing comprises: Part of the initiator includes a first initiator and a second initiator; The first initiator and the second initiator are respectively configured into the first initiator aqueous solution and the second initiator aqueous solution; After subjecting the first initiator aqueous solution and the pre-emulsion to a first polymerization, the pre-emulsion and the second initiator aqueous solution are subjected to a second polymerization to obtain the copolymer emulsion; D. the mass ratio of the remaining initiator to the monomer mixture is 0.1-1:100; E. The monomer mass concentration in the monomer mixture is 25%-35%; F. the total mass of monomers in the monomer mixture accounts for 50% to 90% of the total mass of monomers in the copolymer emulsion; G. The remaining initiator is configured into a remaining initiator aqueous solution before use, and the mass concentration of the remaining initiator aqueous solution is 5%-15%; H. The temperature of the fourth mixing is 50°C-95°C, and the time is 1h-10h; I. the endpoint pH value of the fifth mixing is 7-9; J. The end point solid content of the fifth mixing is 5%-7%; K. the number of parts of the reactive surfactant for the fifth mixing is 0.5 parts to 10 parts; L. The amount of the reactive surfactant used in the sixth mixing is 0.5 to 3 parts.

8. The method for preparing a lithium ion battery binder according to claim 7, characterized in that: At least one of the following conditions is met: A. the concentration of the first initiator aqueous solution is 1Wt%-20Wt%; B. the concentration of the second initiator aqueous solution is 1Wt%-15Wt%; C. The mass ratio of the first initiator to the second initiator is 0.5:1-1:2; D. The temperature of the fourth mixing is 68°C-78°C, and the time is 2h-4h.

9. A lithium ion battery, characterized in that: A lithium ion battery binder and a silicon-carbon negative electrode material prepared by the preparation method of the lithium ion battery binder according to any one of claims 1 to 4 or the lithium ion battery binder according to any one of claims 5 to 8.

10. An electrical equipment, characterized in that: Includes the lithium ion battery as claimed in claim 9.